Deep mantle roots and continental emergence: implications for whole-Earth elemental cycling, long-term climate, and the Cambrian explosion. Issue 4 (12th March 2018) - Lee, Cin-Ty A.; Caves, Jeremy; Jiang, Hehe; Cao, Wenrong; Lenardic, Adrian; McKenzie, N. Ryan; Shorttle, Oliver; Yin, Qing-zhu; Dyer, Blake
ABSTRACT: Elevations on Earth are dominantly controlled by crustal buoyancy, primarily through variations in crustal thickness: continents ride higher than ocean basins because they are underlain by thicker crust. Mountain building, where crust is magmatically or tectonically thickened, is thus key to making continents. However, most of the continents have long passed their mountain building origins, having since subsided back to near sea level. The elevations of the old, stable continents are lower than that expected for their crustal thicknesses, requiring a subcrustal component of negative buoyancy that develops after mountain building. While initial subsidence is driven by crustal erosion, thermal relaxation through growth of a cold thermal boundary layer provides the negative buoyancy that causes continents to subside further. The maximum thickness of this thermal boundary layer is controlled by the thickness of a chemically and rheologically distinct continental mantle root, formed during large-scale mantle melting billions of years ago. The final resting elevation of a stabilized continent is controlled by the thickness of this thermal boundary layer and the temperature of the Earth's mantle, such that continents ride higher in a cooler mantle and lower in a hot mantle. Constrained by the thermal history of the Earth, continents are predicted to have been mostly below sea level for most of Earth's history, with areas of land being confined to narrow strips of active mountain building. Large-scale emergence of stable continents occurred late in Earth's history (Neoproterozoic) over a 100–300 million year transition, irreversibly altering the surface of the Earth in terms of weathering, climate, biogeochemical cycling and the evolution of life. Climate during the transition would be expected to be unstable, swinging back and forth between icehouse and greenhouse states as higher order fluctuations in mantle dynamics would cause the Earth to fluctuate rapidly between water and terrestrial worlds.